Implementing an Online Learning Platform in an English as a Second Language Context: Analyses of Blended Courses Issues and Solution - Rusli, Rusreena; Hashim, Harwati (International Journal of Engineering and Technology, 2018)
Blended learning has turned into an instructive course that has an effect in the present language classrooms. It is accustomed to bring the digital world and in-class teaching together. However, some teachers are yet apprehensive about teaching language in blended learning and students can be irresponsible in managing their learning autonomy. The aim of this paper is to analyse the literature regarding the implementation of blended learning in an English as a Second Language (ESL) context. The research questions are to identify the issues and challenges in the implementation and propose possible solutions from the literature. Document analysis is used on twenty four previous studies conducted from year 2003 to 2018. Findings revealed four main issues and challenges namely teachers; students’ attitude; management of the institutions; and technical support and infrastructure for blended courses to work at the targeted context. This paper found the significance of conducting needs analysis, finding solid foundation for the technical team, proposing appropriate curricula for blended courses, staff training and providing students’ supportive measures as several recommendations to manage the issues in blended learning implementation. This paper assists the required parties to strategize effective actions in order to build successful blended courses in the future.